Finding sustainable solutions for childhood under-nutrition in India: an assessment of association of childhood under-nutrition with multiple factors - Chatterjee, Keya; Sinha, Rajesh; Kumar, Praveen (International Journal Of Community Medicine And Public Health, 2022)
Background: Burden of malnutrition among children is very high in India. Under-nutrition is an interplay of different factors. The present study tried to understand the correlation between child under-nutrition and different distal and proximate factors. Methods: Correlation coefficients (r), using state wise data, were calculated to assess relationship between child nutritional status and other factors such as minimum acceptable diet, micronutrient deficiencies, IYCF, maternal nutritional factors, women agency, water and sanitation practices, HDI, food insecurity and climate change vulnerability. Results: Minimum acceptable diet showed negative correlation with childhood wasting (-0.41) and stunting (-0.36). They were positively correlated with any form of anaemia and vitamin A deficiency. Both basic and age-appropriate immunisation was negatively correlated with wasting (r=-0.2 and -0.5 respectively) and stunting (r=-0.5 and -0.7 respectively). Maternal nutritional factors (BMI<18.5 kg/m2 and any form of maternal anaemia) were positively correlated with childhood nutritional status. Strong negative correlation of both wasting and stunting were found with households having toilet facilities (r=-0.7 in both cases). Indoor air pollution was positively correlated with wasting (r=0.6) and stunting (r=0.2). Both wasting (r=-0.50) and stunting (r=-0.70) were negatively correlated to HDI. Food insecurity and climate change vulnerability were positively correlated with both wasting (r=0.3 for both case) and stunting (r=0.6 and 0.40 respectively). Conclusions: A synergetic programme that brings together essential nutritional interventions and those that address underlying and basic causes is required to sustainably address childhood under-nutrition in India.